2000
DOI: 10.1080/110241500750008961
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic or Open Cholecystectomy: A Prospective Randomised Trial to Compare Postoperative Pain, Pulmonary Function, and Stress Response

Abstract: LC gives significantly better results in terms of less postoperative pain, better pulmonary function, better arterial oxygenation, and shorter hospital stay and duration of sick leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…The remaining 13 articles [14,15,16,17,18,19,20,21,22,23,24,25,26], whose publication period ranged from 1992 to 2005, met the selection criteria and were included in the meta-analysis (table 1). Among the selected articles, 5 were randomized trials [15, 16, 18, 22, 25] and the other 8 were nonrandomized [14, 17,19,20,21, 23, 24, 26]. Thus, the final analysis considered a total of 680 patients: 297 underwent open cholecystectomy and 383 laparoscopic cholecystectomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 13 articles [14,15,16,17,18,19,20,21,22,23,24,25,26], whose publication period ranged from 1992 to 2005, met the selection criteria and were included in the meta-analysis (table 1). Among the selected articles, 5 were randomized trials [15, 16, 18, 22, 25] and the other 8 were nonrandomized [14, 17,19,20,21, 23, 24, 26]. Thus, the final analysis considered a total of 680 patients: 297 underwent open cholecystectomy and 383 laparoscopic cholecystectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, considering intra-admission outcomes, we found that laparoscopic cholecystectomy is associated with a faster recovery, shorter hospitalization, lower mortality rate, less postoperative pain and a better pulmonary function [13,14,15,16,17,18,19,20,21,22,23,24,25,26]. All these outcomes linked to the post-admission period, reflect the quality of care during the admission.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies were performed in patients undergoing cholecystectomy, mainly showing a less pronounced postoperative increase in C-reactive protein, IL-1 and IL-6 for the laparoscopic approach, while the results of the systemic cellular changes differed between the different studies [9, 10, 13, 18, 22, 25, 27, 30, 32, 34, 39, 44]. Redmond et al [34]as well as Walker et al [44]found significantly lower levels of leukocytes and different leukocyte subsets after laparoscopic cholecystectomy, while other groups could not detect any difference between the groups with regard to the cellular parameters during the postoperative course.…”
Section: Clinical Trials Comparing the Impact Of Laparoscopic And Conmentioning
confidence: 99%
“…Prospective randomized and non-randomized trials have compared the postoperative changes in immunologic and inflammatory parameters of different surgical procedures [6, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46](table 1, 2). Most studies were performed in patients undergoing cholecystectomy, mainly showing a less pronounced postoperative increase in C-reactive protein, IL-1 and IL-6 for the laparoscopic approach, while the results of the systemic cellular changes differed between the different studies [9, 10, 13, 18, 22, 25, 27, 30, 32, 34, 39, 44].…”
Section: Clinical Trials Comparing the Impact Of Laparoscopic And Conmentioning
confidence: 99%
“…However, in 20% -30% of patients significant pain and dyspeptic symptoms still persist (8)(9)(10)(11)(12)(13)(14)(15)(16). Laparoscopic cholecystectomy (LC) offers marked and definite advantages with regards to early ambulation, decreased duration of hospital stay, less postoperative pain, improved postoperative pulmonary function, decreased or equivocal post-op complication rates and decreased time to return to normal day to day activities as has been demonstrated in both randomized controlled trials (17)(18)(19) and cohort studies (20)(21)(22). After subjecting patients of symptomatic gallstones to cholecystectomy, some patients still persist with various symptoms after procedure.…”
Section: Introductionmentioning
confidence: 99%